Centralized and Local Color Doppler Ultrasound Reading Agreement for Diagnosis of the Chronic Cerebrospinal Venous Insufficiency in Patients with Multiple Sclerosis - Caprio, Maria G.; Marr, Karen; Gandhi, Sirin; Jakimovski, Dejan; Hagemeier, Jesper; Weinstock-Guttman, Bianca; Zivadinov, Robert; Mancini, Marcello (Current Neurovascular Research, 2017)
Background: An impaired cerebrospinal venous drainage was postulated to be a cofactor in the multifactorial pathogenesis of multiple sclerosis (MS). Chronic cerebrospinal venous insufficiency (CCSVI) is characterized by abnormalities of the main extracranial cerebrospinal venous outflow routes, which can be detected by color Doppler Ultrasound (CDUS) using 5 venous hemodynamic (VH) criteria. Discrepant results between different investigators were reported in the past, therefore the usefulness and applicability of the CCSVI CDUS-based diagnosis in clinical research and practice has been questioned. The reproducibility of proposed criteria for CCSVI detection depends on the blinding, training level, skills of the operator and interpretation of VH criteria. Objectives: To assess agreement between centralized and local reading of CDUS examination for diagnosis of CCSVI in trained Doppler sonologists. Methods: This study was performed in 78 MS patients and 28 age- and sex-matched healthy controls (HCs). Extracranial and transcranial CDUS venous hemodynamic assessment was conducted, according to International Society of Neurovascular Disease (ISNVD) recommended criteria, by a single CCSVI-trained expert sonologist blinded to the subject disease status. After the local Doppler sonologist performed the investigation, all images and video clips of the CDUS examination were sent to the centralized reading center, where a second blinded reading was performed by two CCSVI-trained expert sonologists. Statistical analyses were performed comparing accuracy of CCSVI diagnosis (≥2 VH criteria) and each of the 5 individual VH criteria using Cohen kappa statistic, along with positive/negative agreement and Odds ratio (OR) with 95% confidence intervals (95% CI). Results: Diagnosis of CCSVI was obtained in 59.7% of local and 64.3% centralized readers (Kappa, 0.67, p<0.001). Similar Kappa values were obtained for CCSVI diagnosis and individual CCSVI criteria in both MS patients and HCs. The highest Kappa between local and centralized readers was observed for VH criteria 5 (0.93) followed by VH criteria 4 (0.70), VH criteria 1 (0.66), VH criteria 2 (0.64) and VH criteria 3 (0.58). The positive predictive value (PPV) and negative predictive value (NPV) for CCSVI diagnosis were 82.7% and 86,7%, respectively with an OR of 31.1 (95% CI 11.1-87.5, p<0.001). The highest agreement between local and centralized readers was observed for VH criteria 4 (OR 98.7, 95% CI 17.1-569.9, p<0.001) with 72.7% PPV and 97.3% NPV followed by VH criteria 5 (53, 95% CI 13.4-209.2, p<0.001) with 98.1% PPV and 100% NPV value. Conclusion: Centralized reading of the CDUS examination for the diagnosis of CCSVI is feasible with high accuracy in CCSVI-trained Doppler sonologists. The most reproducible VH criteria between local and centralized readers were VH criteria 4 and 5.
Keywords: Color doppler ultrasound